Lemierre Syndrome Due to Staphylococcus Aureus Infection and Presenting with Periorbital Cellulitis and Bilateral Abducens Nerve Palsy - Pierre, Lara Linhares; Cisne, Ana Camille Feijão; Pierre, Lucas Linhares; Pierre-Filho, Paulo de Tarso Ponte (Brazilian Journal of Case Reports, 2025)
Lemierre syndrome is an uncommon and potentially fatal condition characterized by head or neck infection, thrombosis/thrombophlebitis of the internal jugular vein, and septic embolization to distant organs. This case report describes a 56-year-old male patient who made a home pimple drainage that resulted in periorbital cellulitis with progression to internal jugular vein thrombosis and septic embolism. Ophthalmological examination revealed bilateral abducens nerve palsy. Blood culture was positive for Staphylococcus aureus. He was managed with broad-spectrum antibiotics and anticoagulation. Response to treatment was satisfactory. Lemierre syndrome should be suspected in patients with bacteremia and radiologic imaging of pulmonary embolism or internal jugular vein thrombosis/ thrombophlebitis, even in the absence of signs and symptoms of oropharyngeal infection. Furthermore, uncommon pathogens should be considered conditions, based on the suspected source of primary infection.